Preliminary approach to improve knowledge management in engineering management - Abdul-Rahman, H.; Wang, C. (Academic Journals, 2010)
There is a steady change in engineering management from an information age to knowledge age where there is an increasing need for knowledge management. The construction industry has a poor record in the management of its knowledge, and results in huge wastage of resources and detrimental effect to quality. In addition, knowledge management in the context of the Malaysian construction industry has many available gaps for improvement. As such, a study amongst Malaysian construction professionals as a preliminary approach to improve the practice of knowledge management has been initiated. The objectives of this study are to identify the effectiveness of previous knowledge management practices and to determine critical factors that can promote and improve the standard of knowledge management. Both quantitative and qualitative approaches including questionnaire surveys, semi-structured interviews, and a participant observation case study have been employed. Crucial knowledge management enablers are thoroughly identified in this study. Critical factors for optimization have been recommended to improve the knowledge management efficiency in engineering.